Design and Implementation of Smart and Low Cost Multi-task Farming System Using Arduino - Shasi Kiran, Uppu; Arya, Shanu; Rajasekaran, M (International Journal of Engineering and Technology, 2018)
Using the idea of IOT this project explain the multi-task farming system using Arduino. The system uses a Wi-Fi module in which system is connected to the internet. A motor and two valve are controlled by this module for transporting the water to the farm on Â receiving the signal from a water level sensor and soil moisture indicator. This system explain the illustration of Internet of Things (IOT). This concept does the work like weeding, spraying water, harvesting, etc. The system also does the work like determining the humidity of the soil and measuring the physical environmental factor which can be monitored by any individual from anywhere they want and the data gets recorded in the database of the webpage or the app through IOT connection and the individual gets a notification on their cellular phone through message so that he can operate the system through a push message or can be done through the mobile app if there is any requirement to the field that to be taken care of.Â Â